UPAYA PENCEGAHAN KEJAHATAN CYBERBULLYING PADA REMAJA MELALUI PLATFORM INSTAGRAM: STUDI KASUS DI SMKN X JAKARTA - Aenul Farodisa; Intan Khoirunnisa; Putri marcellina; Rania Yasmine Fadli; Dinda najwa mutiara rizqy; Eunike Angelica sarambe (PT. Hasba Edukasi Mandiri, 2025)
The development of digital technology has led to the widespread use of social media among teenagers, but it also presents various risks, including cyberbullying. This study aims to examine crime prevention efforts against cyberbullying among adolescents through the Instagram platform, using a case study at SMKN X Jakarta. The research applied a qualitative approach with a case study method. Data were collected through interviews, observation, and documentation, and analyzed thematically. The findings reveal that cyberbullying practices at the school are largely influenced by deviant traditions, such as the